Emerging technologies for education : first International Symposium, SETE 2016, held in conjunction with ICWL 2016, Rome, Italy, October 26-29, 2016, Revised selected papers /: first International Symposium, SETE 2016, held in conjunction with ICWL 2016, Rome, Italy, October 26-29, 2016, Revised selected papers. (2017) - Unknown
No abstract available